Genome-Wide Identification and Analysis of Chitinase GH18 Gene Family in Mycogone perniciosa - Yang, Yang; Sossah, Frederick Leo; Li, Zhuang; Hyde, Kevin D.; Li, Dan; Xiao, Shijun; Fu, Yongping; Yuan, Xiaohui; Li, Yu (Frontiers in Microbiology, 2021)
Mycogone perniciosa is the mycopathogen causing wet bubble disease of Agaricus bisporus. Its secreted chitinases are not only used to degrade the cell wall of host edible fungi but also for its growth and development. Based on our reported genome sequence of highly pathogenic strain Hp10 of M. perniciosa and comparative genomic analysis with other pathogens, we found its chitinase glycoside hydrolase (GH) 18 gene family underwent the vast expansion. We identified 41 GH18 genes in M. perniciosa Hp10 and carried out bioinformatics and expression pattern analysis. The bioinformatics analysis results showed 41 GH18 genes were distributed on 11 contigs and divided into three groups and eight subgroups based on conservative domains, and each group contains a different number of introns and exons. Phylogenetic analysis with the other 15 filamentous fungi demonstrated its classification results were consistent with conservative domains. Combined with the transcriptomic results of different stages of M. perniciosa-infected A. bisporus, we found that 24 GH18 genes were differentially expressed in different infected stages, some genes were significantly increased in the middle and late stages of infection, and the proportion and types of GH18 genes significantly upregulated in different infection or development stages are different. It is speculated that the GH18 gene family has functional differentiation in the evolution process, and different types of genes may have different functions. Among these GH18 genes, five represented different groups were selected for RT-PCR and gene cloning to verify the accuracy of sequencing. The results showed that they could successively be expressed in different infection stages, which were consistent with the previous sequencing results. Based on the above results, the regulation model of the GH18 gene family expression was clarified, laying the foundation for further study of the infection mechanism and pathogenic key genes of M. perniciosa.